The influence of tick prices on high-frequency trading on market quality in LQ-45 Indonesia - Riyanto, Agus; Sriyana, Jaka; Arifin, Zaenal; Sutrisno (International Journal of Management and Sustainability, 2024)
This research aims to determine the influence of tick prices on high-frequency trading on market quality in LQ-45 Indonesia. This study employs a quantitative approach. This study employed the Fixed Effect, Random Effect and Common Effect. The research data source used secondary data, with 37 stocks identified that met the criteria for High-Frequency Trading (HFT). The data analysis technique utilized panel data method. Three findings were revealed in the results of this research: first, it demonstrates a significant impact of tick price on High-Frequency Trading (HFT) activity; second, it reveals a positive influence of HFT on market quality, as evidenced by the metrics of spread, volatility, and risk-adjusted return. HFT activity in this research substantiates a positive impact on market quality, measured through spread, volatility, and risk-adjusted return. However, when assessing market quality based on liquidity, the research indicated that HFT volume and trades exert a noteworthy impact on diminishing market liquidity; and third, High-Frequency Trading (HFT) generally exhibits a notable impact on reducing spreads, even though its strength is not conclusively proven in the HFT volume test. The practical implications of this research offer insights into the positive impact of tick prices on the escalation of High-Frequency Trading (HFT) activity.